The Correlation Between Family Support and Family Self-Efficacy with Relapse in Individuals with Schizophrenia - Andari, Made Ayu; Karin, Putu Ayu Emmy Savitri; Suarningsih, Ni Kadek Ayu; Sulistiowati, Ni Made Dian; Wisnawa, I Nyoman Dharma (Babali Publisher, 2024)
Introduction: Schizophrenia is a common illness in mental hospitals, often leading to recurrent relapses. These relapses can be influenced by both internal and external factors, including family support and self-efficacy in caring for individuals with schizophrenia (IWS). Good family support benefits IWS, whereas poor support can worsen their condition. High self-efficacy in families is essential for providing optimal care. This study examines the correlation between family support and family self-efficacy with relapse in IWS in the Puskesmas (Community Health Centre) III North Denpasar area. Methods: A quantitative descriptive correlational study with a cross-sectional approach was conducted. The research instruments included a family support questionnaire and the General Self-Efficacy Scale (GSES). Data were collected through door-to-door surveys from May to June 2024, involving 68 respondents who were family members of IWS. Results: Many respondents were aged 46-55, had a high school education, and earned below the minimum wage. The Pearson correlation test showed a strong negative correlation between family support and relapse (p = 0.00, r = -0.62) and between family self-efficacy and relapse (p = 0.00, r = -0.61). Multivariate analysis using multiple linear regression indicated that family support (β = -0.37) had a slightly stronger influence on relapse occurrences in IWS compared to family self-efficacy (β = -0.36). Conclusion: Enhancing family support and self-efficacy is crucial in minimising relapse in IWS. Families should be encouraged to strengthen their role in providing support and improving their self-efficacy in caregiving.